PROFILES OF ENFORCEMENT AND SURVEILLANCE IN JAVA SEA FISHERIES: A CLOSER LOOK AT THE CIRCUMSTANCES OF PEMALANG AND DEMAK REGENCIES - Indah Susilowati (JOURNAL OF COASTAL DEVELOPMENT, 2002)
Compliance is necessary for successful management of the fisheries. In fact, to secure compliance, enforcement and surveillance, which are quite costly, are needed . It is realized that enforcement inputs in Indonesia is limited and not sufficient to watch the waters of this country. Therefore, it needs a lot of effort to improve the enforcement and surveillance schemes. It is necessary to find out new alternatives or paradigms of monitoring, controlling and surveillance (MCS) in such a way in order to ensure the sustainability of the fisheries resource.